Penyuluhan Kesehatan Masyarakat melalui Skill Training Antisipasi COVID-19 dengan Busami (Pembuatan Handsanitizer Alami) Kelompok PKK di Kelurahan Sawah Ciputat - Munarsih, Munarsih; Savitri, Shela Indah; Putren, Irenne; Wilandari, Devi Fitria; Abdurohman, Dede (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Handsanitizer is a non-rinsed hand sanitizer that is useful for preventing the spread of covid-19. Through Community Service Activities, it is expected to increase understanding and insight about management science and specifically in the field of health management. PKM are carried out as an effort to provide health education and training skills in the manufacture of natural handsanitizers as well as to become material for study and input for PKK women Sawah Ciputat Urban Village women to be able to implement them in their daily activities in the pandemic era Covid-19. This activities was carried out through a lecture method by inviting PKK women to be actively involved in Community Service Activities organized by the Faculty of Business Management at University of Pamulang. Community Service activities were carried out on May 20-21, 2020. The results of the Community Service activities concluded that basically PKK women in Sawah Village had quite good abilities in the practice of making handsanitizers. This is evident from their abilities to practice making and using handsanitizers in a way, there are good and right. The expectation of this Community Service activities are quality and creativity in making handsanitizers continue to increase and they dare to market handsanitizers. Then, they can be improve their economies.